Gideon the ninth - Muir, Tamsyn (Muir, Tamsyn. Locked tomb trilogy, 2019)
The Emperor needs necromancers. The Ninth Necromancer needs a swordswoman. Gideon has a sword, some dirty magazines, and no more time for undead nonsense. Tamsyn Muir<U+2019>s Gideon the Ninth unveils a solar system of swordplay, cut-throat politics, and lesbian necromancers. Her characters leap off the page, as skillfully animated as arcane revenants. The result is a heart-pounding epic science fantasy. Brought up by unfriendly, ossifying nuns, ancient retainers, and countless skeletons, Gideon is ready to abandon a life of servitude and an afterlife as a reanimated corpse. She packs up her sword, her shoes, and her dirty magazines, and prepares to launch her daring escape. But her childhood nemesis won<U+2019>t set her free without a service. Harrowhark Nonagesimus, Reverend Daughter of the Ninth House and bone witch extraordinaire, has been summoned into action. The Emperor has invited the heirs to each of his loyal Houses to a deadly trial of wits and skill. If Harrowhark succeeds she will be become an immortal, all-powerful servant of the Resurrection, but no necromancer can ascend without their cavalier. Without Gideon<U+2019>s sword, Harrow will fail, and the Ninth House will die. Of course, some things are better left dead.